Hubungan Efek Samping Penggunaan Obat Antihipertensi Terhadap Disfungsi Ereksi Pada Pria - Salman; Arline Rahmadianti Kusumawardhani; Eka Wulan Galuh Pratiwi; Mutiara Alfiah; Sepvia Putri S; Sofianti Hidayat (Journal of Pharmaceutical and Sciences, 2023)
Side effects or negative effects of antihypertensive drugs are often associated with the frequency of excessive urination and decreased sex drive such as erectile dysfunction. Erectile dysfunction is the inability of men to achieve and maintain an erection of the penis adequate to satisfy sexual intercourse. This study aimed to explain the relationship between the side effects of antihypertensive use and erectile dysfunction. The method used in writing this scientific paper is in the form of a literature study carried out by collecting relevant journals in the period of January to March 2023. The databases used are Google Scholar and PubMed. Based on 20 research journals from 1991 to 2023, it is known that antihypertensives that often cause side effects on erectile dysfunction are diuretics and beta-blockers, except nebivolol and clonidine by altering the sympathetic flow, affecting corporal smooth muscle contractions, and affecting androgen hormone levels. Based on the results obtained, it can be concluded that there is a relationship between the use of antihypertensive drugs and erectile dysfunction.